Analisis Bibliometrik: Pengaruh Inovasi Hijau dan Ekonomi Sirkular Terhadap Kinerja UKM di Indonesia - Andre Erlando Septian Sitinjak; Syarifa Hanoum (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
SMEs contribute significantly to global carbon emissions, making the implementation of green innovation and the circular economy crucial for improving performance while ensuring environmental sustainability. The circular economy is an economic concept focused on waste reduction and the reuse of resources through strategies such as recycling, reuse, and sustainable design. This concept aims to create a regenerative economic system by minimizing the exploitation of natural resources and reducing negative environmental impacts. Meanwhile, green innovation refers to the development and application of environmentally friendly innovations in products, processes, and business models to enhance resource efficiency and reduce industrial emissions and waste. This study aims to analyze the influence of both concepts on SME performance. Data were collected from 479 articles indexed in the Scopus and Web of Science (WoS) databases, and analyzed using co-occurrence, co-citation, and bibliographic coupling techniques with the help of VOSviewer software. The findings indicate that green innovation and the circular economy significantly enhance SME performance, particularly in terms of operational efficiency, competitiveness, and market reputation. Green innovation dimensions, such as green process and product innovation, are proven to support business performance, while circular economy indicators in social, economic, and environmental aspects serve as key factors for sustainability. This study provides strategic insights for SMEs to integrate green practices into their business strategies in order to achieve long-term competitive advantage.